Cutaneous afferent activity in median and radial nerve fascicles: a microelectrode study. Issue 9 (September 1975) - Burke, D; Mackenzie, R A; Skuse, N F; Lethlean, A K
Abstract : Cutaneous afferent activity was recorded in fascicles of the median and radial nerves of normal subjects using percutaneous microelectrodes. Multi-unit fascicular responses were dominated by activity in large myelinated fibres. Easily tolerated electrical stimuli evoked the full spectrum of fast and slow myelinated fibre activity but more intense levels were required to activate unmyelinated fibres. Correlation of the evoked potentials and the sensations reported by the subject suggested that fast myelinated fibres mediate tactile sensations. Pricking pain appeared with the activation of slow myelinated fibres. The only sensations induced by electrical stimuli were tactile or painful.